Reflections on project-based learning: A case study in formative assessment and feedback in a Pediatric Emergency discipline during the pandemic - Tiago Perez Leitão Maciel (2022)
Introduction The experience acquired in the Professional Master's Program in Teaching in Health at a Brazilian public university, in the course of the subjects of "Student Assessment" and "Advance in Teaching Methods: Assessment and Feedback in the Classroom" led to the development of strategies in a specific discipline to implement different virtual skills from active methodologies, especially in the context of the current pandemic with greater assimilation and durability of knowledge for students in the health area. Objectives: to share a teaching-learning experience centered on formative assessment using feedback in a virtual environment as a tool with the production of practical and innovative academic content. Methods: Case study with a qualitative approach; applying a questionnaire on the perception of formative assessment, feedback and satisfaction with the teaching method used. Results Four professors and 50 undergraduate medical students participated in this experience, 46% male and 54% female aged between 23 and 33 years. The innovation in the delivery of content and types of assessment with the production of educational products, in a continuous process of interaction between teachers and students and between them, corroborated the concept of formative assessment with improvement in teaching and learning as reported by 100% of students; Final considerations: the use of active methodologies associated with digital technologies as a strategy to achieve a better formative assessment in the pandemic scenario that we still face seemed to be an important strategy.